Analysis Of Variance in Realization of Spending Budget at Class II Bandung Port Health Office - Karmana, Dedi; ZN, Michelle Kayla; Nasution, Sakti Muda; Fudsy, Mira Ismirani (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
This study uses quantitative descriptive techniques to examine the fluctuations in budget implementation at the Bandung Class II Port Health Office from 2020 to 2023. The data was collected using observation, interviews, documentation, and web data searches. The research findings indicate variations in the actualization of the budget from one year to another. The budget realization rate 2020 stood at 92.75%, indicating a high-efficiency level in budget utilization despite challenges encountered in buying items and implementing programs. The budget realization for 2021 witnessed a notable increase to 95.78% owing to enhancements in the planning and monitoring system and enhanced interdepartmental coordination. Nevertheless, the percentage of realization is expected to experience a minor decline to 95.08% in 2022 due to technical issues in procurement and alterations in policy. 2023, there was a further decline, with a budget realization rate of 92.59%. This fall was primarily due to economic instability and changes in the organizational structure. Variance analysis reveals that specific spending categories routinely exhibit discrepancies between the intended budget and its implementation, including the amount allocated for training and human resource development. The variation results from shifts in priorities, limitations in time, and challenges encountered during the program's implementation. Managerial and technical capacity in financial management is a factor that affects variation. Despite implementing financial management training, there is still room for improvement. The findings of this study emphasize the necessity for enhancements in the budget planning procedure that are characterized by greater participation, stricter budget monitoring, higher utilization of information technology, and enhanced managerial and technical proficiency. This study offers a thorough analysis of the fluctuations in budget implementation and the factors that impact it, along with suggestions for enhancing the efficiency and efficacy of budget utilization at the Bandung Class II Port Health Office. By gaining a more profound comprehension of budget realization variances, these agencies can develop more efficient techniques to oversee their budgets, enhance accountability and transparency, and deliver superior public services. This research aims to serve as assessment and reference material for relevant agencies, assisting in enhancing budget management and significantly contributing to public health at ports.